2010
DOI: 10.5465/amr.35.1.zok27
|View full text |Cite
|
Sign up to set email alerts
|

Open Versus Closed Innovation: A Model of Discovery and Divergence

Abstract: When is open innovation superior to closed innovation? Through a formal simulation model we show that an open approach to innovation allows the firm to discover combinations of product features that would be hard to envision under integration. However, when partners have divergent goals, open innovation restricts the firm's ability to establish the product's technological trajectory. The resolution of the tradeoff between benefits of discovery and costs of divergence determines the best approach to innovation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
208
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(214 citation statements)
references
References 33 publications
4
208
0
2
Order By: Relevance
“…Greenstein (1996) has noted that openness in the aerospace industry increases costs because it requires the cooperation of multiple suppliers in a complementary configuration. Almirall and Casadesus-Masanell (2010) also concluded that openness has drawbacks, which they even quantify as a divergence cost, suggesting that when a product or system is opened to outside actors, control over design and development of the technology is weakened. These themes all point in the direction of closure.…”
Section: Open and Closed Innovationmentioning
confidence: 99%
“…Greenstein (1996) has noted that openness in the aerospace industry increases costs because it requires the cooperation of multiple suppliers in a complementary configuration. Almirall and Casadesus-Masanell (2010) also concluded that openness has drawbacks, which they even quantify as a divergence cost, suggesting that when a product or system is opened to outside actors, control over design and development of the technology is weakened. These themes all point in the direction of closure.…”
Section: Open and Closed Innovationmentioning
confidence: 99%
“…The knowledge coming into the firm from highly embedded IFRs is likely redundant, so it may serve to distract and overwhelm the innovating firm's internal effort, rather than add strength or resources [2]. The firm tries to use its R&D expertise and knowledge to drive innovation but is significantly hindered by the lack of unique information flowing into its structural boundaries.…”
Section: Moderating Role Of Randd Intensitymentioning
confidence: 99%
“…The firm tries to use its R&D expertise and knowledge to drive innovation but is significantly hindered by the lack of unique information flowing into its structural boundaries. Research suggests that highly embedded relationships can derail a technology development trajectory by limiting creativity and restricting access to fresh ideas [2]. This benefit, coupled with the firm's struggle to sort out and evaluate knowledge redundancy from the same highly embedded IFRs, combines to hinder firm platform innovation.…”
Section: Moderating Role Of Randd Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Almirall and Casadesus-Masanell (2010) suggest that an open approach to innovation, which might include markets for inventions, can allow firms to discover new combinations of product features that would be less likely to emerge if R&D efforts were 'closed'. However, this beneficial effect comes with the drawback of reducing the possibility of firms controlling the trajectory of their innovation processes.…”
Section: Innovationmentioning
confidence: 99%